Diagnosis of compaction in soils cultivated with corn in the Fraylesca Region, Chiapas - López Báez, Walter; Reynoso Santos, Roberto; López Martínez, Jaime; Camas Gómez, Robertony; Tasistro, Armando (Revista Mexicana de Ciencias Agrícolas, 2018)
Soil compaction is a problem recently identified as one of the main constraints on the maize surface of the municipality of Villaflores in the region of The Frailesca, Chiapas, due to this, it needs to be studied with greater precision. The objective of this study was to characterize the problem of compaction on the mechanized surface cultivated with corn in the New Mexico commn. We studied 177 plots, in which the apparent density, organic matter and texture were determined at the depths of 0-20 and 20-40 cm. The owners of the properties were interviewed to obtain information about their cultivation practices and corn productivity levels. The results show that 83.3% of the studied area presented superficial compaction and 94.6% compaction in the subsoil (plow floor). The producers pointed out that in years with critical periods of drought the yields are reduced by 58%, which is correlated with the decrease of the porosity as a result of the compaction. The main causes of the compaction were the intensive tillage with machinery 100% of the sites, the very low content of 100% organic matter and the type of soil (luvisols and acrisols). The attention of the compaction problem requires a comprehensive corrective and preventive strategy that should take as a central element the elevation of the contents of organic matter, to reverse the current unsustainable management of the land.
Keywords: corn, soil, unsustainable management